Interface Between Newly Formed Dentine and Mineral Trioxide Aggregate: A Preliminary Scanning Electron Microscopy Study - Parirokh, Masoud; Asgary, Saeed; Eghbal, Mohammad Jafar; Stowe, Sally; Ghoddusi, Jamileh (Iranian Endodontic Journal, 2010)
INTRODUCTION: This study was carried out to investigate calcific tissue formation against mineral trioxide aggregate (MTA) after pulp capping. MATERIALS AND METHODS: The pulps of six teeth from four dogs were exposed and capped with MTA. After extraction each tooth was sectioned into halves. Each half was then further sectioned in the mesiodistal or buccolingual direction. Calcified tissue of the capped area was examined from either the pulpal side or in profile view using scanning electron microscopy and focused ion beam imaging. RESULTS: The results from all views showed that MTA crystals were in direct contact with calcified tissue. Calcified bridges after focused ion beam preparation showed the same pattern that were seen by scanning electron microscopy in profile view. Newly deposited dentine and early phase of calcosphirit structures could clearly be distinguished from older tubular dentine. CONCLUSION: MTA when used as a pulp capping agent could produce calcific tissue in underlying pulp.